Activation of Pre-mRNA Splicing by Human RNPS1 Is Regulated by CK2 Phosphorylation - Trembley, Janeen H.; Tatsumi, Sawako; Sakashita, Eiji; Loyer, Pascal; Slaughter, Clive A.; Suzuki, Hitoshi; Endo, Hitoshi; Kidd, Vincent J.; Mayeda, Akila (Molecular and Cellular Biology, 2005)
Article Usage Stats Services MCB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue MCB About MCB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy MCB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0270-7306 Online ISSN: 1098-5549 Copyright © 2014 by the American Society for Microbiology. For an alternate route to MCB .asm.org, visit: MCB